Eating Disorders and Disordered Eating Behaviors in Cystic Fibrosis: A Neglected Issue - Anastasia Petropoulou; Georgia Bakounaki; Maria G. Grammatikopoulou; Dimitrios P. Bogdanos; Dimitrios G. Goulis; Tonia Vassilakou (MDPI AG, 2022)
As with the majority of chronic diseases having specific nutrition recommendations, in cystic fibrosis (CF), the emphasis placed on patients regarding their diet and ideal body weight status often increases the risk of developing disordered eating behaviors and by inference, eating disorders (EDs). Body weight appears to be an important concern for patients with CF, with many patients struggling to lose weight. Between sexes, women appear more preoccupied with dieting compared to men, but exhibit a better body image, mainly due to their preference for a lower weight. Several comorbidities appear to change these dynamics, and visibly apparent factors, including scars, ports, and tubes, and the need for supplementary oxygen supply, may also influence body image perception. Disordered eating is usually initiated during a bout of pulmonary infection, with the patient feeling unwell to eat. Regarding the prevalence of EDs, research appears conflicting on whether it is higher among individuals with a CF diagnosis or not. As for comorbidities, anxiety and depression consist of the most common psychiatric diagnoses in CF, also greatly prevalent in EDs. Despite the plethora of studies, non-specific CF tools, small samples, and lack of data regarding important outcomes, including lung health, indicate the need for more research.